窗帘 • 自白 • 闺情 ： 李清照的闺情词研究 = Study on Li Qingzhao's Guiqing Ci-poetry - 林晓庆 Lim, Hsiao Qing (2015)
“闺情”一词出现于南朝梁简文帝萧纲的诗题，写出了女子心绪不定的状况。后来，“闺情”题材多写女子于闺房中思念在外的丈夫。所以“闺情”可以定义为“闺中所发之情”。但是，“闺情”的场域不仅仅局限于闺房之中，也包括庭院、女子在闺房中所观之物、所发之情等等。李清照作为第一女词人，其作品往往与家国、社会、政治联系在一起，或被评价为“颇有丈夫气”。这些论述虽都有理，但是笔者认为，李清照的词之所以动人，更重要的因素是因为女子本身的生活经验和细腻的感情。因此，本文集中于李清照的闺情词，看李清照如何利用闺房内的 “窗”、“帘”意象制造出富有层次的空间与感情。另外，也将探讨李清照在闺房内的自我观照，看她如何利用闺房为场域，抒发女子忧愁、寂寞、无奈、不安等复杂情绪。除此之外，笔者概括了前人对“易安体”的定义与效仿，再对笔者认为的“易安体”核心价值为“闺情”这一论点进行论述。“Guiqing”（闺情） was first discovered as a poem’s title of Emperor Liang of Jianwen. It dictates the emotional side of a woman. Then, “Guiqing” was used to express longingness of a woman towards her husband in her chamber. “Guiqing” can be defined as females ’emotion in chamber. However, “Guiqing” does not have to be limited in personal bedroom but also includes courtyard, objects, and emotions that a woman felt in her chamber. As the first female poet, Li Qingzhao’s ci-poetry always associates with nation, politics, and society issues. In the author’s opinion, the charm of Li Qingzhao’s cipoetry is her meticulous description of a woman’s living experience and the exquisiteness feelings. Therefore, this thesis aims to study how Li-Qing Zhao’s use the image of “window” and “curtain” to create an extraordinary feelings and imaginary space. Other than that, author will go into details about how Li Qingzhao uses her chamber as a setting to express a woman’s sorrow, loneliness, helplessness, insecurity and complicated feelings. The author has also compiled the definition and imitation of Yi-an style（易安体）, concluding the viewpoint of “Guiqing” is the core value of “Yi an style”.